The Child and Youth Profile: A Toolkit to Facilitate Cross-Disciplinary Educational Planning. (Kairaranga, 2017)
Collaboration is an essential component of optimal educational planning. In order to collaborate effectively, it is important that information from all of those involved with the learner is used to develop a multi-dimensional understanding of the child/youth. Yet the identification, sharing and collating of this key information can be a difficult process due to lack of time, a focus on specialist jargon, and lack of tools or expertise. In this article, we introduce a toolkit, called the New Zealand Child and Youth Profile, to assist educational teams to discuss key aspects of children’s functional experiences and abilities to inform educational planning. The toolkit is inspired by the International Classification of Functioning, Disability, and Health for Children and Youth (ICF- CY) but contextualised for New Zealand. The toolkit has recently been piloted and revised based on user feedback and is available for teams interested in using it to facilitate cross-disciplinary educational planning.